2018
DOI: 10.33422/ejest.2018.07.80
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Improved Mechanical Properties of 1100 Aluminium Alloy via Particle Reinforcement

Abstract: In this study, metal matrix composite is fabricated on 1100 Aluminium alloy by multi pass friction stir processing using different reinforcement particles namely Fly Ash, Palm Kernel Shell Ash, Ti62222 and 304 Stainless steel. Metal matrix composites with average grain size of 6.5 μm are achieved. The addition of reinforcements at the stir zone has enhanced the mechanical properties of the 1100 Al alloy, finer grain structure is also evident after three cumulative passes. Higher strength ranging from 268 to 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The MMCs gained 26.60% more hardness and 16.10% more strength after the addition of 3.75% fly ash and 3.75% graphite. The use of fly ash in MMCs has also been investigated in other research, and they have shown benefits in mechanical characteristics and wear resistance over the basic alloy [100][101][102][103][104][105][106][107]. The mechanical qualities reported in this research, which used fly ash as the only reinforcement or as a supplementary reinforcement, are summarized in Table 3.…”
Section: Fly Ashmentioning
confidence: 92%
“…The MMCs gained 26.60% more hardness and 16.10% more strength after the addition of 3.75% fly ash and 3.75% graphite. The use of fly ash in MMCs has also been investigated in other research, and they have shown benefits in mechanical characteristics and wear resistance over the basic alloy [100][101][102][103][104][105][106][107]. The mechanical qualities reported in this research, which used fly ash as the only reinforcement or as a supplementary reinforcement, are summarized in Table 3.…”
Section: Fly Ashmentioning
confidence: 92%